A hybrid shrinking projection method for common fixed points of a finite family of demicontractive mappings with variational inequality problems - Suthep Suantai (2018)
© 2017 by the Tusi Mathematical Research Group. In this article, we prove some properties of a demicontractive mapping defined on a nonempty closed convex subset of a Hilbert space. By using these properties, we obtain strong convergence theorems of a hybrid shrinking projection method for finding a common element of the set of common fixed points of a finite family of demicontractive mappings and the set of com- mon solutions of a finite family of variational inequality problems in a Hilbert space. A numerical example is presented to illustrate the proposed method and convergence result. Our results improve and extend the corresponding results existing in the literature.